2021
DOI: 10.33448/rsd-v10i4.13392
|View full text |Cite
|
Sign up to set email alerts
|

Atitudes relacionadas a colaboração interprofissional entre os profissionais da Atenção Primária em Saúde

Abstract: O estudo buscou caracterizar as atitudes relacionadas à colaboração interprofissional entre os profissionais de saúde da Atenção Primária em Saúde de um município no Maranhão. Para isso, foi realizado um estudo transversal com 173 profissionais de saúde. Foram aplicados questionários sobre a colaboração interprofissional, com a Escala Jefferson de Atitudes Relacionadas à Colaboração Interprofissional, e sobre aspectos demográficos, de formação e atuação profissional deles. Os dados foram organizados em planilh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 25 publications
2
2
0
7
Order By: Relevance
“…Overall, scale scores were high for all academic programs, demonstrating positive student attitudes toward collaboration. This result is similar to those of research carried out in Primary Care, (10)(11)(12) which showed a high mean score for different professionals.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Overall, scale scores were high for all academic programs, demonstrating positive student attitudes toward collaboration. This result is similar to those of research carried out in Primary Care, (10)(11)(12) which showed a high mean score for different professionals.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies carried out in Brazil showed EJARCI´s good internal consistency. (9)(10)(11) Despite this, the only other study with Brazilian students (13) demonstrated a low Cronbach's Alpha Coefficient (0.42), probably because of its small sample size.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations